The Sexual Division of Labor and the Split Paycheck. (2016) - Hirschmann, Nancy J.
Abstract : This essay takes up an apparently minor idea of Susan Moller Okin's Justice, Gender, and the Family —that employers should split the paycheck of wage‐earning husbands between employees and their stay‐at‐home spouses—and suggests that it actually threatens to undermine Okin's entire argument by perpetuating the most central cause of women's inequality by Okin's own account: the sexual division of labor. Recognizing the vital contributions that Okin's seminal work made and the impact that it had on the field of feminist philosophy and political theory, the essay explores the ethical, political, and philosophical problems with this solution to the dire problems of gender inequality and injustice that Okin correctly identifies. The essay suggests that her commitment to liberalism may have resulted in a commitment to an inadequate vision of how to solve the problems of gender inequality, and offers other possibilities that Okin could have pursued instead that sustain her strong commitment to liberalism.